Dream weaving: A conversation with Jennifer Irwin. Issue 1 (1st June 2021) - Anderson, Margot
In December 2019 as I made my way through Bangarra Dance Theatre's exhibition Knowledge Ground, Australia was in the early stages of a devastating bushfire season and Sydney was shrouded in a cloud of smoke. It was Bangarra Dance Theatre's 30th anniversary and I was fully immersed in a theatrical display of set pieces, soundscapes and costumes from landmark productions by Australia's premier First Nations performing arts company. Bangarra's body of work draws on over 65, 000 years of Indigenous culture and fuses the language of traditional and contemporary dance to create a compelling narrative based on a shared knowledge of country. These works have served as markers of revelation in the development of my own understanding of Australia and have made Bangarra an internationally acclaimed source of powerful story telling. They have also fuelled a long-lasting appreciation of the costumes designed for the company by Jennifer Irwin with whom I shared a series of discussions.